2010
DOI: 10.1542/peds.2009-3245
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Surgery Outcomes in Down Syndrome: Analysis of a National Clinical Database

Abstract: Background Contemporary outcomes data in Down Syndrome (DS) patients undergoing congenital heart surgery are limited. We describe patient characteristics and post-operative morbidity and mortality in a large multi-center cohort. Patients and Methods This retrospective cohort study utilized The Society of Thoracic Surgeons Congenital Heart Surgery Database to compare patient characteristics and postoperative outcomes in DS and non-DS patients (0–18y) undergoing surgery from 2000–2008. Primary analysis focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
172
2
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(196 citation statements)
references
References 24 publications
(21 reference statements)
11
172
2
11
Order By: Relevance
“…[11][12][13]23 Surprisingly, little is known about the outcomes of children with DS after surgical correction of congenital cardiac defects other than an AVSD. 24 An enhanced understanding of the association between DS and survival across a broad spectrum of lesions may improve our ability to optimize the care of these infants and children.…”
mentioning
confidence: 99%
“…[11][12][13]23 Surprisingly, little is known about the outcomes of children with DS after surgical correction of congenital cardiac defects other than an AVSD. 24 An enhanced understanding of the association between DS and survival across a broad spectrum of lesions may improve our ability to optimize the care of these infants and children.…”
mentioning
confidence: 99%
“…However, as previously noted [7], the reported mortality difference was primarily in the earlier years of the study [9] when infants with AVSD and DS probably received unequal cardiac care [7]. All recent contributions have clearly demonstrated that with the current level of care, DS is not a risk factor for primary surgical correction of complete AVSD [1][2][3][4][5][6][7]. Moreover, some studies have even suggested that DS in patients with complete AVSD may be considered a protective factor for surgical correction [1,3,5] and for long-term follow-up experience [1,2] due to the more favorable cardiac anatomy.…”
mentioning
confidence: 75%
“…Esta temática se encuentra fuera del objetivo de esta actualización, no obstante, el lector puede encontrar revisiones sobre esta materia 9,36,37 .…”
Section: Patología Cardíacaunclassified
“…El riesgo de mortalidad por sepsis en estos pacientes aumenta un 30% tras corrección de factores de confusión 8 . Asimismo, las complicaciones respiratorias e infecciosas post-cardiocirugía son más comunes resultando en estadías más prolongadas en la unidad de cuidados intensivos (UCI) 9 .…”
Section: Introductionunclassified